Fazlur Rahman and His Enduring Legacy for Indonesian Islamic Scholarship - Wekke, Ismail Suardi (PT Maju Malaqbi Makkarana, 2025)
This article examines Fazlur Rahman's intellectual legacy and its influence on the development of Islamic thought in Indonesia. Rahman, with his neo-modernist approach, offered a